Prevalence of arterial hypertension in the elderly: A literature review (Research, Society and Development, 2023)
Systemic arterial hypertension, in an uncompensated way, affects the cognitive activities of the central nervous system, presenting itself in a subtle way, being an aggravation in elderly patients, thus generating a risk factor for this age group. Objectives: to show the prevalence of arterial hypertension in the elderly in an intensive care environment. Methodology: This study refers to an integrative literature review prepared in accordance with the six steps. This method is guided by the checklist recommended by PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses). In the first search, 5 studies were selected and, in the second, 15 more, both with the application of the eligibility criteria, namely: full text; time frame of the last 5 years; languages in Portuguese and Spanish; that are relevant to the topic. Results: Systemic arterial hypertension commonly affects elderly people over 60 years of age, with a prevalence of up to 65% in this age group. The Caretaker device is a technology created for monitoring blood pressure in order to obtain beats by beats, in addition to information regarding the interval between the closing of the heart valves. Arterial hypertension in Brazil has a prevalence of approximately 24.8% in adults, females with a higher proportion (26.8%) compared to males (22.5%).